(untitled) (Balneo and PRM Research Journal, 2022)
Abstract: Background: Osteoarthritis is one of the most common causes of pain and musculoskeletal disability and mainly affects the middle-aged and the elderly. The condition is chronic and disabling, it diminishes the patients’ quality of life. Purpose. The study had the purpose of pointing out a possible connection between physical activity and the reduction of pain accompanied by the increased functional capacity in patients with chronic degenerative diseases during the COVID-19 pandemic. Material and method: The study was conducted on an outpatient basis for a period of 6 months on a number of 40 patients diagnosed with osteoarthritis. The evaluation of the patients was made at the beginning of the treatment and at its end (after 4 weeks), as well as at the control after 12 weeks. Results: The study included a number of 40 patients over 45 years old, divided into 2 study groups: in group L1-knee osteoarthritis and in group L2 -hip osteoarthritis. The therapeutic physical exercise reduced pain and stiffness, and it also improved the functional capacity. Conclusions: Therapeutic physical exercise has an important role in the reduction of pain and disability, as well as in the increase in the quality of life, if it is done properly. Keywords: osteoarthritis, therapeutic physical exercise, pain, pandemic COVID-19